2013
DOI: 10.3329/bjmb.v4i2.13773
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Insulin resistance: Etiopathegenesis and influencing factors

Abstract: Metabolic syndrome and insulin resistance has been the subject of much debate over the last two decades. Its pathophysiologycal basis, however, still remains to be clearly understood. Both genetic and environmental factors have been implicated in its pathogenesis. Mutation of genes encoding signal transduction molecules of insulin and acquired factors like aging, diets, physical activity, obesity and related molecular changes, dyslipidemia, hypertension and smoking were proposed by many groups. This review exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The metabolic syndrome (MetS),as comprised of visceral obesity, dyslipidaemia, hyperglycaemia, and hypertension, has become one of the major challenges in clinical medicine as well as in publichealthworldwide [1][2][3] .MetS is a cluster of interrelated risk factors whichshows higher susceptibilityto cardiovascular disease (CVD) by 2-fold increase of risk and type 2 diabetes mellitusby 5-fold 4 and that tends to come to an effect within 5-10 years spanin an apparently healthy individual 5 -as itis evident that subjectively healthy individuals may have biochemical abnormalities along with presence of MetS 6,7 . The identification ofmodifiable CVD risk factors and predictors of MetS inan otherwise healthy population is necessary in order toidentify individuals who may benefit from early interventions 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic syndrome (MetS),as comprised of visceral obesity, dyslipidaemia, hyperglycaemia, and hypertension, has become one of the major challenges in clinical medicine as well as in publichealthworldwide [1][2][3] .MetS is a cluster of interrelated risk factors whichshows higher susceptibilityto cardiovascular disease (CVD) by 2-fold increase of risk and type 2 diabetes mellitusby 5-fold 4 and that tends to come to an effect within 5-10 years spanin an apparently healthy individual 5 -as itis evident that subjectively healthy individuals may have biochemical abnormalities along with presence of MetS 6,7 . The identification ofmodifiable CVD risk factors and predictors of MetS inan otherwise healthy population is necessary in order toidentify individuals who may benefit from early interventions 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Menopause is accompanied with a redistribution of body fat resulting in central obesity and insulin resistance which were found to largely increase the prevalence of MetS in postmenopausal females 30 . Additionally, several biological changes take place during menopause and might aid indeveloping insulin resistance and MetS including oxidative stress, inflammatory changes, and postmenopausal alterations in adipocytokine production and lipid utilization 31,32 . These facts broadly elucidate the obvious acceleration in cardiovascular diseases (CVD) in females post menopause 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Several other studies also emphasized that utilization of fruits as compare to juices are associated with a lower risk of diabetes, especially among women 24,25,26 . A meta-analysis showed that fruit juice has a borderline significant effect on reducing diastolic blood pressure, but had no effect on systolic blood pressure 27,28 .…”
Section: Introductionmentioning
confidence: 99%